2021
DOI: 10.46303/ressat.2021.41
|View full text |Cite
|
Sign up to set email alerts
|

Learning Styles and Instructional Materials as Correlates of Grade 6 Learners`' Mathematics Performance in Buffalo City, South Africa

Abstract: Mathematics is a core subject in South Africa. Studies have shown that the performance of learners on this subject is not encouraging. Many factors have been alluded to by scholars as contributing factors to this poor performance. The gap between theory and practice of mathematics teaching can be bridged by the use of appropriate learning styles, availability, and utilization of instructional. This paper finds out the relationship that exists among learning styles, instructional materials, and mathematics perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 11 publications
1
6
1
4
Order By: Relevance
“…The same result was obtained by Adu et al (2020), who reported that visual learning is predominant among South African students, and Cabual (2021), who found that visual is reportedly the 'new normal' learning style. In contrast, Alog (2012) discovered that the predominant learning styles among the 5th and 6thgrade students in her study of intermediate public schools are auditory and visual, respectively.…”
Section: Learning Stylesupporting
confidence: 77%
See 2 more Smart Citations
“…The same result was obtained by Adu et al (2020), who reported that visual learning is predominant among South African students, and Cabual (2021), who found that visual is reportedly the 'new normal' learning style. In contrast, Alog (2012) discovered that the predominant learning styles among the 5th and 6thgrade students in her study of intermediate public schools are auditory and visual, respectively.…”
Section: Learning Stylesupporting
confidence: 77%
“…The result resembles the findings of Alog (2012), who claimed that pupils' learning style was unrelated to their academic achievement in Mathematics. However, this opposes the findings of Adu et al (2020), Sinaga (2022), andVillajuan (2019). The result suggests that students may still have poor number sense competency regardless of learning style.…”
Section: Level Of Number Sense Competencycontrasting
confidence: 66%
See 1 more Smart Citation
“…We hypothesized that motor competence, not MVPA, would be related to improved cognitive and academic skill development in early childhood. For this study, 283 children were recruited from 13 community-based preschools (55% female; M = 4.2 years old, SD = .6; 41% non-Hispanic White, 37% non-Hispanic Black; 10% Hispanic, 10% mixed race, 2% Asian, 1% American Indian, Australia (Sianturi et al, 2022), Chile (Huincahue et al, 2021), Reino Unido (Muncer et al, 2022), Chipre (El-Adl & Alkharusi, 2020), Sudáfrica (Adu & Duku, 2021), Rusia (Sheromova et al, 2020), Turquía (Baltaci et al, 2016), Israel (Nahmias & Teicher, 2020).…”
Section: Metodologíamentioning
confidence: 99%
“…Relationship between teaching styles and students' conditions, meaning that students learn well when taught with methods that align with their learning styles. Varied, effective, and efficient teaching styles will underlie teachers' design and implement learning models that vary depending on the learning material delivered (Adu & Duku, 2021;Bernacki et al, 2021;Moon, 2022). A fun learning model will give a distinct impression on the development of elementary school students (Arioder et al, 2020;Bulkani et al, 2022;Fauziah et al, 2020).…”
Section: Introductionmentioning
confidence: 99%